desi - Kisbianty, Desi (JURNAL AKADEMIKA, 2017)
Research Institution and Community Service of STIKOM Dinamika Bangsa Jambi, in executing its function, that is to manage all activity in term of research and community service is not optimum yet. One of those is at publication activity. This is caused by unproper control set in quality assurance as the benchmark of the publication activity. The goals of the research is to create quality assurance model at publication activity in Research Institution and Community Service (LPPM). The model is described by using case diagram, activity diagram and calss diagram. This kind of model is considered able to be a reference for LPPM in system building and execxuting quality assurance internally in STIKOM Dinamika Bangsa Jambi. Keywords : Quality Assurance, Information System, Publication, UML